Literature Review: Comparison of Glossy and Matte Lamination on Posters to Enhance Visual Appeal - Rafa Ayu, Nur Aini; Dianta Mustofa Kamal (Marasofi International Media and Publishing (MIMP), 2026)
Posters remain a strategic medium in visual communication due to their ability to attract attention quickly and convey information efficiently in public spaces. Beyond graphic design elements such as layout, typography, and imagery, surface finishing plays a critical role in shaping visual perception, readability, and audience response. Among the most widely used finishing techniques, glossy and matte (doff) lamination exhibit distinct optical, psychological, and functional characteristics that directly influence communication effectiveness. This study aims to comparatively review glossy and matte lamination applied to posters through a narrative literature review approach. Peer-reviewed journal articles, conference proceedings, and authoritative books indexed in reputable databases including Scopus, Web of Science, IEEE Xplore, ScienceDirect, SpringerLink, and Google Scholar were systematically collected. A total of 42 relevant publications published between 2013 and 2023 were selected and thematically synthesized. The review reveals that glossy lamination enhances color vibrancy and contrast through specular reflection, thereby increasing immediate visual attraction, but often introduces glare that compromises readability and visual comfort. In contrast, matte lamination provides superior readability and reduced visual fatigue under diverse lighting conditions, conveying a professional and elegant impression, although with slightly reduced color saturation. The findings highlight that lamination selection is not absolute but context-dependent, influenced by message objectives, target audience characteristics, and installation environment. This review also identifies significant research gaps, particularly in neuro-cognitive audience response measurement, long-term durability under tropical environmental conditions, and cross-cultural perception of surface finishes. Based on these gaps, a structured research roadmap is proposed. The study contributes an evidence-based framework to support designers, printing practitioners, and visual communication scholars in making informed finishing decisions.